Enhancing the resilience of micro food and beverage businesses in Malaysia: an evaluation critical success factors approach / Noor Azmi Ahmad, Azdel Abdul Aziz and Aliffaizi Arsat - Ahmad, Noor Azmi; Abdul Aziz, Azdel; Arsat, Aliffaizi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
This research examines the influence of critical success factors (CSFs) on micro businesses in the food and beverage (F&B) industry in Kuala Lumpur, with a specific focus on their role in fostering resilience in the aftermath of the pandemic. The study aims to explore how these factors contribute to the sustenance and growth of resilient businesses. The food and beverage business has been profoundly affected by the COVID-19 epidemic, leading to considerable challenges for enterprises in sustaining their operations. These challenges arise from a combination of reduced demand, disruptions in the supply chain, and escalated operating expenses. A quantitative research methodology was employed to collect data from small company owners in the Kuala Lumpur area, utilising a self-administered questionnaire as the datagathering instrument. The data collection method involved the participation of eighty business proprietors. Correlation and regression studies were performed to ascertain the association between the variables under investigation. The results indicate a significant association between critical indicators of success, such as brand reputation, exceptional customer service, reliable delivery, and product innovation, and the overall performance and adaptability of a company. This study offers a comprehensive analysis of the critical determinants of success in the food sector in Kuala Lumpur. It is a helpful reference for scholars and organisations while providing practical insights for small-scale food enterprises. Moreover, this research provides insights into the significance of these Critical Success Factors (CSFs) as a source of competitive advantage for micro businesses operating in the Food and Beverage (F&B) sector in Kuala Lumpur and similar environments. Specifically, it highlights their importance in ensuring the sustainability and robustness of business operations. In brief, the study results provide valuable insights for F&B microbusiness owners on how to address obstacles and establish robust operations. The study underscores the significance of these critical success factors (CSFs) in ensuring the long-term sustainability and prosperity of these businesses within the constantly changing business environment.